Increasing railway capacity with the installation of reactive power compensation - L. A. German (Вестник Научно-исследовательского института железнодорожного транспорта)
The article considers existing regulated installations of transverse capacitive compensation for increasing the capacity of sections of the traction network of 25 and 2×25 kV of Russian railways. Characteristics of a static reactive power generator based on bipolar IGBT transistors (manufactured by LLC NPP “RU-Engineering”, Naberezhnye Chelny), a switchable filtercompensating unit (manufactured by the Gorkovskaya Railway and the Nizhny Novgorod branch of SamGUPS), a three-stage switchable filter-compensating unit. To increase the capacity, all installations are switched on at the traction network sectioning posts. Long-term operation of the static reactive power generator and switchable filter-compensating unit have proven their operational efficiency. At the same time, the following upgrades are proposed: in a static reactive power generator it is proposed to reduce the installed power, replacing it with unregulated compensation, and in a switchable filter-compensating installation, it is proposed to switch in 400–500 V steps to normalize the traction mode of the electric rolling stock.It is shown that in terms of technical characteristics, a switchable filter-compensating installation with a thyristor switch is not inferior to a static generator of reactive power in terms of increasing the capacity, and in some respects it surpasses it. On the whole, in terms of payback period, a switchable filter-compensating installation surpasses a static generator of reactive power due to the high cost of the latter. The following options for using the considered installations are proposed. With the required power of transverse capacitive compensation units up to 5–6 MVAr, to increase the capacity, switchable filter-compensating units should be installed. Taking into account real loads, such a solution will be implemented at most sectioning posts. For installations with a capacity of more than 5–6 MVAr, the option of using a static reactive power generator of reduced power should be considered: at high loads, its efficiency will increase.